Concealing Cipher Data using an Amalgam of Image Steganography and two-level Image Cryptography - Bhowmick, Anirban; Kapur, Vishal; Paladi, Surya Teja (International Journal of Computer Sciences and Engineering, 2015)
With the mounting significance of data security over the network, steganography and cryptography are two emerging fields of research. Steganography is the technique in which confidential data is concealed in a cover medium. Cryptography is an approach of translating the personal data to some unintelligible form to keep it safe from intruders. Steganography and Cryptography attempt to accomplish identical objective of data security via different means. In this paper, the authors state a novel system to mask secret data. The confidential text is encrypted using modified Playfair cipher in the first step. In the second step, the cipher text is subjected to image steganography. In this step, the cipher text is embedded into the image using LSB encoding. To further enhance the concealment of the message, the image is subjected to a two-level simple but secure symmetric key encryption which comprises of two image encryption algorithms. These encryption algorithms use two pseudo random number generators that is Linear Congruential Generator and Blum Blum Shum algorithm.